Strategies To Overcome The Damages Caused By Covid-19 In The Hotel Industry - Kariru, Antoneta Njeri; Ndungu, David Mwangi (Machakos University Press, 2021)
The year 2019 saw the emergence and spread of the coronavirus disease or covid-19 pandemic. The pandemic has moreover led to service interference, low customer demand, loss of traditional markets, reduced revenue, job losses, destroyed assets, reputation risks, higher operating costs and business closures in the hotel industry. Studies nonetheless indicate that the hospitality industry is not committed to crisis management and hotels tend to be reactive to crises. This means that the hotels do not plan ahead for the management of crises and resultant losses. However, the tourism industry has always recovered from crises like fires, terrorism attacks, political disturbances and natural disasters including tsunamis and floods. This review paper consequently facilitates proactive planning by exploring strategies that hotels can adopt to overcome the damages caused by covid-19. The recommended strategies include cost reduction, revenue management, insurance, internal marketing, product development, market re-strategizing, staff re-training, embracing the crises management approaches especially proactive planning, business continuity planning and crisis communication, seeking government assistance and applying for tourism relief funds. The paper concludes that the covid-19 crisis has created challenges and opportunities for the hotel industry. For example, by losing one market segment, the hotels get the opportunities to re-strategize and develop new products and markets. The pandemic has also stimulated technological innovations and advancements in the industry including robotic temperature scanners, disinfectants and sanitizers, keyless technologies and mobile applications. The paper therefore adds to existing strategies, policies and body of knowledge on the management of covid-19 in the hotel industry.
Keywords: Covid-19; Damages; Strategies; Hotels